Transcendentalist Hermeneutics : Institutional Authority and the Higher Criticism of the Bible - Grusin, Richard A. (Book collections on Project MUSE., 1991)
American literary historians have viewed Ralph Waldo Emerson's resignation from the Unitarian ministry in 1832 in favor of a literary career as emblematic of a main current in American literature. That current is directed toward the possession of a self that is independent and fundamentally opposed to the "accoutrements of society and civilization" and expresses a Transcendentalist antipathy toward all institutionalized forms of religious observance. In the ongoing revision of American literary history, this traditional reading of the supposed anti-institutionalism of the Transcendenta.